2021
DOI: 10.1111/edt.12673
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision‐making for a post‐traumatic malocclusion in an elderly patient: A case report.

Abstract: Traumatic dental injuries in elderly patients are a rising trend due to demographic and social changes of the population. Older dentulous patients in good health have become increasingly common. The development of a post‐traumatic malocclusion is a common sequela resulting from mandibular condyle fracture, as in the case reported in this paper. The decision‐making process led the authors to rule out conservative treatment options and to perform orthognathic surgery on an 81‐year‐old patient, an unprecedented r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…While it has been suggested that clinical guidelines often oversimplify treatment decision-making regarding implants, numerous studies highlighted the importance of considering multiple factors before selecting, preparing, or saving implants, particularly the patient’s medical history, bone quality, and implant location [ 30 , 75 , 76 , 77 ]. This was echoed by studies investigating surgical, extractive, and sedative decision making, which suggest consideration of patient factors such as medical history, including oncological prognosis and the level of dental anxiety [ 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it has been suggested that clinical guidelines often oversimplify treatment decision-making regarding implants, numerous studies highlighted the importance of considering multiple factors before selecting, preparing, or saving implants, particularly the patient’s medical history, bone quality, and implant location [ 30 , 75 , 76 , 77 ]. This was echoed by studies investigating surgical, extractive, and sedative decision making, which suggest consideration of patient factors such as medical history, including oncological prognosis and the level of dental anxiety [ 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%